SROI analysis in measuring the success of the Partnership Program as a form of CSR of PT Petrokimia Gresik - Aurashafa, Dita Amelia; Premananto, Gancar Candra (Southeast Asian Business Review, 2024)
Corporate Social Responsibility (CSR) is a form of social investment companies make, hoping it will bring long-term benefits. An investment must be measurable and accountable. Corporate Social Responsibility certainly involves both internal and external stakeholders. By using a qualitative approach, this research aims to find out the stakeholders of the Partnership Program, one of PT Petrokimia Gresik's social responsibilities, along with the benefits received by each stakeholder. This research also aims to determine the social impact obtained from each fund invested by the company in that CSR Program using the SROI method. From calculations using the SROI method, a ratio of  5.32:1 is obtained, which means that every Rp 1 invested by the company will generate an impact of Rp 5.32. The results of this measurement are important for the company as an evaluation material for implementing the Partnership Program in the next period to produce a more significant, effective, and efficient impact.